Caribou conservation and recovery in Ontario: development and implementation of the Caribou Conservation Plan - Armstrong, Ted (E.R.); Gluck, Michael; Hooper, Glen; Mettam, Iain; Racey, Gerald D.; Rondeau, Marc (Rangifer, 2012)
The range of Ontario’s woodland caribou (Rangifer tarandus caribou) (forest-dwelling ecotype) has receded northward substantially over many decades, leading to its current Threatened designation. Ontario released its Caribou Conservation Plan (CCP) in the fall of 2009. This policy responded to public input and recommendations from the Ontario Woodland Caribou Recovery Team and the Caribou Science Review Panel, and outlines conservation and recovery actions to conserve and recover caribou. Within an adaptive management framework, the CCP builds upon a recent history of managing at large landscape scales in Ontario to implement a range management approach as the basis for recovery actions. These commitments and actions include enhanced research and monitoring, improved caribou habitat planning at the landscape scale, an integrated range analysis approach using advanced assessment tools to evaluate thresholds of habitat amount, arrangement and disturbance, the assessment of probability of persistence, consideration of cumulative effects, meeting forest management silvicultural performance requirements, consideration of caribou recovery implications when managing other wildlife, an initial focus on the southern edge of caribou distribution where threats are most significant, improved outreach and stewardship, and consideration of Aboriginal Traditional Knowledge in recovery actions. Implementation of the CCP signifies a long-term provincial commitment to caribou recovery, initially focusing on identified priorities within the CCP.